Penerapan Sistem E-Learning Pada PT. Hibaindo Armada Motor Jakarta Timur Serta Keterkaitannya dengan Prestasi Kerja Dengan Indikator Pengetahuan dan Kualitas Kerja - Samroh (Program Studi Administrasi Bisnis POLITEKNIK LP3I BANDUNG, 2019)
The purpose of this research is to know the correlation between elearning system with job performance obtained from indicator of knowledge and work quality. The research was conducted by qualitative descriptive method with phenomenology approach with respondents of PT. Hibaindo Armada Motor Jakarta numbering 30 people. Researchers found new fact that there is link between elearning system with quality work and knowledge, employees assume that elearning system bring changes to self-development and increase knowledge, then researchers dig further by doing questionnaire in the form of four closed questions related to knowledge and quality of work. From these points obtained that employees are greatly assisted with the elearning system, then increase the confidence during service or during discussion of questions and answers. Researchers found that this elearning phenomenon into a technological breakthrough that allows employees to develop independently.